2020
DOI: 10.1002/rcs.2182
|View full text |Cite
|
Sign up to set email alerts
|

Novel C‐arm based planning spine surgery robot proved in a porcine model and quantitative accuracy assessment methodology

Abstract: Background We assessed pedicle screw accuracy utilizing a novel navigation‐based spine surgery robotic system by comparing planned pathways with placed pathways in a porcine model. Methods We placed three mini screws per vertebra for accuracy evaluation and used a reference frame for registration in four pigs (46 screws in 23 vertebrae). We planned screw paths and performed screw insertion under robot guidance. Using C‐arm and CT images, we evaluated accuracy by comparing the 3D distance of the placed screw he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…robotic-assisted pedicle screw placement with intraoperative 3D image-based planning, our method using C-arm-based images yielded similar results. 20,24,25,28,29 Furthermore, the mean values for each offset type were 1.78 mm, 2.3 mm, and 2.64°, respectively, which are comparable or superior to those reported by other studies. [30][31][32] In the case of the patient as well as the cadaver, when screws were inserted there was the force of which surroundings such as muscle and skin push the instruments and screws.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…robotic-assisted pedicle screw placement with intraoperative 3D image-based planning, our method using C-arm-based images yielded similar results. 20,24,25,28,29 Furthermore, the mean values for each offset type were 1.78 mm, 2.3 mm, and 2.64°, respectively, which are comparable or superior to those reported by other studies. [30][31][32] In the case of the patient as well as the cadaver, when screws were inserted there was the force of which surroundings such as muscle and skin push the instruments and screws.…”
Section: Discussionsupporting
confidence: 79%
“…Although a prior study used intraoperative C‐arm‐assisted robot screw placement in a porcine model, clinical trial results have not been reported. However, compared with the clinical trial results of robotic‐assisted pedicle screw placement with intraoperative 3D image‐based planning, our method using C‐arm‐based images yielded similar results 20,24,25,28,29 . Furthermore, the mean values for each offset type were 1.78 mm, 2.3 mm, and 2.64°, respectively, which are comparable or superior to those reported by other studies 30–32 …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“… 55 Finally, Curexo® is a robot-assisted spine surgery system that uses a C-arm-based navigation system. 52 Kim et al. reported that accuracy rates for pedicle screws placement were less accurate than in other studies on human patients (Grades A+B: 80.4%), 52 which may be attributed to the fact that the robot is still at a developmental stage.…”
Section: Discussionmentioning
confidence: 92%
“…Several robotic systems like CIRQ® (Brainlab Germany), 49 Excelsius GPS® (Globus Medical), 50 Mazor X (Mazor Robotics Ltd., Caesarea, Israel), 51 and Curexo® (Curvis-spine, South Korea) 52 were not included in our study due to no suitable controlled studies. It has been reported that the lightweight and table-mounted aspects of the new CIRQ® arm are intended to be more ergonomic and less disruptive to operative workflow relative to larger robotic units.…”
Section: Discussionmentioning
confidence: 99%